Implementasi Metode Dan Strategi Pendidikan Islam Dalam Perspektif Al-Qur’ani dan Nabawi Serta Relevansinya Terhadap Pendidikan Kontemporer - Rana Meiyanda; Mutiara Mahardika; Wahyu Ashabul Jannah; Abdul Rahman; Nelson (Universitas Majalengka, 2026)
This article discusses the importance of educational methods in the perspective of the Qur'an and its role in improving the quality of learning. This research uses a qualitative approach to the type of library research, studying relevant literature to gain an in-depth understanding of the methods of education in the Qur'an. The methods identified include dialogue, matching, jidal, narrative, parable, and targhib as well as tarib. Each method has special benefits in raising motivation, facilitating understanding, and creating a conducive learning atmosphere. By applying the right methods, educators can the desired educational goals and help students develop optimally in cognitive, affective, and psychomotor aspects.